Image Quality Assessment for Low-Dose-CT in Hybrid SPECT/CT Imaging - Grosser, Oliver S.; Ruf, Juri; Kupitz, Dennis; Czuczwara, Damian; Loewenthal, David; Thormann, Markus; Furth, Christian; Ricke, Jens; Pech, Maciej; Kreissl, Michael C.; Amthauer, Holger (Nuklearmedizin - NuclearMedicine, 2018)
Objectives: Low-dose-computed tomography (LD-CT) is used in nuclear medicine hybrid imaging (e.g., SPECT/CT) for attenuation correction of emission data and anatomical correlation of findings. However, there are currently no standards for image quality (e. g., detectability) comparable to those for diagnostic CT. Therefore, the aim of this explorative study was to evaluate retrospective LDCT data in terms of CT image quality and detectability of anatomical structures. Methods: Two readers blindly scored abdominal LD-CT images (n = 40 patients) in terms of detectability (n = 20 structures/patient), image quality, and readers’ confidence in scoring the image quality for a clinically hybrid imaging protocol. Results were analysed by ANOVA to identify factors (e. g., anatomical structures) that influenced performance scores. The inter-rater agreement was evaluated by determining the chance-corrected Cohen’s Kappa coefficient. Results: Image noise was acceptable for anatomical correlation in 96.1 % of the readings with an almost perfect inter-rater agreement (KBP = 0.85). A detectability of at least 80 % was observed in 13/20 (KBP ≥ 0.7) and 90 % in 9/20 (KBP ≥ 0.85) of the structures analysed by both readers. The confidence of both readers in scoring image quality was at least sufficient in 98.8 % of the examined patients (KBP = 0.95). Conclusion: Although LD-CT protocols commonly used in hybrid imaging have a poor image quality not suitable for primary CT diagnostics, they enable detection of a variety of anatomical structures. LDCT can therefore also be referenced in the associated reports for anatomical correlation of findings from SPECT imaging.
Keywords: SPECT/CT; Low-Dose-CT; Hybrid imaging; Detectability; Image quality